2018
DOI: 10.1016/j.jjcc.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Angioscopic differences of coronary intima between diffuse and focal coronary vasospasm: Comparison of optical coherence tomography findings

Abstract: These results indicate that the presence of atherosclerotic plaques at the spasm site is likely to be related to the occurrence of a focal vasospasm. This may support the difference of features between focal CS and diffuse CS and contribute to precise treatment for each spasm type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 51 publications
2
27
0
Order By: Relevance
“…This relationship was confirmed in autopsy case reports [26,27]. However, such plaque rupture has not been recognised in this and other studies [10][11][12][13][14]; thus, if present, this mechanism may be rare. Second, severe and repeating coronary spasms may lead to the repeating hypercontraction and extension of the intima, which results in coronary erosion.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This relationship was confirmed in autopsy case reports [26,27]. However, such plaque rupture has not been recognised in this and other studies [10][11][12][13][14]; thus, if present, this mechanism may be rare. Second, severe and repeating coronary spasms may lead to the repeating hypercontraction and extension of the intima, which results in coronary erosion.…”
Section: Discussionsupporting
confidence: 76%
“…Many studies have investigated the relationship between intracoronary thrombus formation and coronary spasm using intracoronary imaging techniques that show intracoronary thrombi in patients with VSA [ 10 , 11 , 12 , 13 , 14 ]. The frequency of intracoronary thrombus formation in patients with VSA might vary depending on the studied patients’ characteristics, such as the presence of ACS or MINOCA or chronic coronary syndrome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research, Kitano et al demonstrated that yellow plaques containing lipids existed more frequently at the segments of focal CAS compared with the segments of diffuse CAS (Kitano et al, 2018). Given that focal CAS is caused by local hyperreactivity to a generalized constrictor stimulus in mild atherosclerosis, the researchers thought that the pathophysiology of diffuse CAS is limited to atherosclerotic lesions (Kitano et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery spasm shows various configurations such as focal spasm, diffuse spasm, or combined spasm and may lead to serious life-threatening arrhythmias in some patients [1]. As noninvasive tests, hyperventilation test and exercise test were performed in the clinic.…”
Section: Introductionmentioning
confidence: 99%